CFD Modeling Of Waste Heat Recovery On The Rotary Kiln System in the Cement Industry - Novia, Novia; Faizal, Muhammad; Liana, Septa (Sriwijaya University, 2013)
The cement production process is one of the most energy and cost intensive in the world. In order to produce clinker, a cement industry requires the substantial energy consumption. About 70% of energy consumption lies on the unit of rotary kiln system. The higher amount of energy consumption is due to the lack of work efficiency tools leading the waste heat. This reserach was focus on modeling of the waste heat recovery in the rotary kiln system using CFD. Analysis of mass and energy balance was used to determine the sources of heat loss from kiln system. The results showed that the distribustion of the input heat to the system is a good agreement with the output energy and gave the significant insights oft the reasons for the low overall system efficiency. The system efficiency is obtained of 53 %. The major heat loss sources have been determined as kiln exhaust (21.88% of total input), cooler exhaust to stack (9.62 % of total input) and heat loss astemated as heat from kiln surface (13.54 % of total input). The amount of heat energy can be absorbed by air amounted to 163,080 Kcal / hour and can be used as air for combustion of fuel. Based on data calculation, the amount of coal can be saved amounted to 738 kg / day.